Anaplastic Large Cell Lymphoma CD30+ ALK- in the Oral Cavity as a Primary Manifestation in HIV+ Patient: Case Report - Leonardi, Nicolás; Caciva, Ricardo Christían; Piemonte, Eduardo David; Brusa, Martín; Sambuelli, Rubén; Allende, Adrián; Panico, René Luis (Journal of Oral Diagnosis, 2019)
Anaplastic large cell lymphoma (ALCL) is a rare subtype of T-cell lymphoma that may involve mucocutaneous sites, in primary form, or secondary to systemic disease. It is a systemic malignancy characterized by an extranodal phenotype that rarely occurs in the oral cavity as the first manifestation of acquired immunodeficiency syndrome. In the primary forms, ALCL stands out for its favorable prognosis, being important to differentiate them clinically from the secondary ones, which have a rapid and aggressive evolution. For its diagnosis, it requires a rigorous physical and clinical examination and a duly oriented anatomopathological and immunohistochemical evaluation. In the present work, a clinical case of ALCL secondary to HIV is presented, detailing clinical characteristics, anatomopathological description, immunohistochemical profile and evolution against treatment.